Jarmark Dominikański 1975 : Gdańsk 2-17 sierpień / B. Bogusławski. - Bogusławski, Bogdan (1941-2019) ([wydawca nieznany], 1975)
Plakat Jarmarku. Przy prawej krawędzi nazwisko autora, w dolnej części plakatu wymienieni organizatorzy.